NECESIDAD DE REFORMAR EL ART. 605 DEL CÓDIGO ORGÁNICO INTEGRAL PENAL, EN RELACIÓN A ESTABLECER LAS DISTINTAS CLASES DE SOBRESEIMIENTO - Rengel Santín, Luz Edid (2016)
In a criminal investigation after the preliminary hearing of the trial the judge shall issue an order of dismissal, with a resolution that ends the process without ruling on the merits, the court decision, in the form of self produces the termination or suspension of the process for lack of evidence that would allow the application of the criminal law to the case, so it makes sense to enter the trial phase. The dismissal set forth in the Code of Criminal Integral be final when the instruction is not clear that given the fact that at first seemed existing and criminal, or has faded final appearance, their authors acted exempt from liability, so, in that case, the termination of the process occurs with res judicata effect at all similar to an acquittal on the merits. There is talk of provisional dismissal when there are only doubts about the commission of the act or on his own, resulting in a mere suspension of the process, no effect of res judicata. . Article 605 of the Code of Criminal Integral mentions one way of dismissal, unlike what was provided in the previous Code of Criminal Procedure, the new law states that the judge or issue an order of dismissal in the following cases: 5 1. When or prosecutor to refrain from prosecuting and, if applicable, that decision is ratified by the superior. 2. When you find that the facts did not constitute a crime or that the facts upon which the or prosecutor has based its allegation is not sufficient to presume the existence of a crime or participation of the accused person. 3. When you find that have been established exclusion causes of illegality. This standard has been deleted kinds of proceedings, in which there are no reasons for the different types of proceedings that were under the previous Code of Criminal Procedure were removed, leaving one as a possible statement the judge, because no is obviously the same provisional dismiss definitely, so it is inconsistent, being necessary to give effect to the different types of dismissal.